Clinical And Cytogenetic Analysis Of Pervasive Developmental Disorder (Pdd), Mental Retardation (Mr) And Broad Autism Phenotype (Bap) From South Indian Population - S.RAJIV; V.G.ABILASH; M.PAPAKUMARI; M.MURUGAN (International Journal of Pharma and Bio Sciences, 2012)
The aim of study is to analyze the clinical and cytogenetic investigation on patients with PDD, MR and BAP from South Indian population. Cytogenetic analysis of 11 patients with PDD, 3 patients with BAP and 12 patients with MR were carried out by using human leukocyte culturing method and clinical analysis were carried out for all the cases with the help of physicians. A significantly higher number of chromosomal aberrations were observed in all groups when compared to the controls (p < 0.001). This study shows the significantly higher number of chromosomal aberrations in all the cases through karyotyping and chromosomal aberration analysis, which has to be further investigated deeply to detect the possible genetic causes of autism to provide genetic counseling, awareness and management of autistic children.